The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from France. (4th May 2017) - Le Manh, Anne
Abstract: In France, the European accounting directive has been implemented via a decree and a ministerial order, issued without any public consultation and which led to an amendment of the Commercial Code and three regulations released by the Autorité des normes comptables, the French standard-setter. Our analysis of those texts reveals that none of them refer to International Financial Reporting Standards (IFRS). We did not find evidence of any reference to IFRS from the Autorité des marches financiers, the French market regulator, in its decisions on the right application of French Generally Accepted Accounting Principles by listed companies. Hence, IFRS seem to have played a minor role in the recent modification of French regulations resulting from the implementation of the European accounting directive.